Implementasi Digital Banking di Kawasan Asia Tenggara - Tania Tri Wahyuni Taha; Sri Astuty; Diah Retno Dwi Hastuti; Irwandi Irwandi; Abd Rahim (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
The increase in digital banking due to the influence of high levels of internet usage makes the process of digital financial services easy. The Internet is growing rapidly, fast and cheap, has the potential to increase productivity and competitiveness of Southeast Asian economies. The study was conducted in 10 Southeast Asian countries, namely Indonesia, Malaysia, the Philippines, Singapore, Thailand, Brunei Darussalam, Myanmar, Vietnam, Laos, and Cambodia. Except for Timor Leste due to limited data in supporting this research. The object of this study is the use of digital banking as a dependent variable, while the exchange rate (Nt), foreign exchange reserves (Cd), and interest rate (Sb) are independent variables. In addition, the amount of money in circulation is M0 & M1 as the moderator variable. The data collection technique is by taking panel data from 2014 – 2023 obtained from the official website, namely Stastika.com, Tranding Economic, Focus Economic, World bank and sources related to this research. The data collection technique in this study was carried out using Eviews12. tests are needed in selecting the most appropriate estimates, namely, the Chow Test, the Hausman Test and the Lagrange Multiplier Test. In the regression of moderation variables using the Moderated Regression Analysis (MRA) interaction model.